Powder evolution and microstructural development of rare-earth modified AlGdNiCoMn high-entropy alloy during mechanical milling - Tunç, Büşra; Somunkıran, İlyas; Özkaya, Serdar; Çelebi, Müslim; Çanakçı, Aykut (Elsevier B.V., 2026)
The evolution of powder characteristics, phase formation, and microstructure in a rare-earth-modified AlGdNiCoMn high-entropy alloy (HEA) was systematically investigated during high-energy mechanical milling. Equiatomic Al, Gd, Ni, Co, and Mn powders were milled for 1–15 h, and their morphological, structural, mechanical, magnetic, and thermal responses were characterized. Progressive milling induced severe plastic deformation, pronounced particle refinement, and enhanced interdiffusion, leading to gradual solid-solution formation. XRD analysis revealed the transformation of elemental phases into a predominantly nanocrystalline BCC solid solution with minor FCC contributions at extended milling durations. The incorporation of Gd, owing to its large atomic radius, generated substantial lattice distortion, which facilitated nanocrystallization and promoted solid-solution strengthening. As a result, microhardness increased significantly, reaching ∼746 HV after 15 h of milling. Magnetic measurements demonstrated a reduction in saturation magnetization with increasing milling time, attributed to lattice strain, chemical disorder, and weakened 4f–3d exchange interactions. DSC analysis indicated defect annihilation and phase reorganization processes. These findings confirm that Gd microalloying, combined with mechanical milling, is an effective strategy for tailoring the microstructural and multifunctional properties of Al-based HEAs. © 2026
Keywords: Algdnicomn Alloy; Gadolinium; High-Entropy Alloys; Mechanical Alloying; Rare-Earth Elements